Immune Intervention in Sepsis - Chen, Jian; Wei, Haiming (Frontiers in Pharmacology, 2021)
Sepsis is a host immune disorder induced by infection. It can lead to multiple organ dysfunction syndrome (MODS), which has high morbidity and mortality. There has been great progress in the clinical diagnosis and treatment of sepsis, such as improvements in pathogen detection technology, innovations regarding anti-infection drugs, and the development of organ function support. Abnormal immune responses triggered by pathogens, ranging from excessive inflammation to immunosuppression, are recognized to be an important cause of the high mortality rate. However, no drugs have been approved specifically for treating sepsis. Here, we review the recent research progress on immune responses in sepsis to provide a theoretical basis for the treatment of sepsis. Constructing and optimizing a dynamic immune system treatment regimen based on anti-infection treatment, fluid replacement, organ function support, and timely use of immunomodulatory interventions may improve the prognosis of sepsis patients.